SweGen dataset from SweGen: A whole-genome map of genetic variability in a cross-section of the Swedish population - Adam Ameur; Robert Karlsson; Patrik Magnusson; Ulf Gyllensten (Uppsala University, 2017)
A high-quality map of genetic variation in the Swedish population based on
a representative cross-section of 1000 individuals.
Keywords: Allele frequency data; Medical and Health Sciences; Medicin och hälsovetenskap